Nicotine Synergizes with High-Fat Diet to Induce an Anti-Inflammatory Microenvironment to Promote Breast Tumor Growth - Thalia Jimenez; Theodore Friedman; Jaydutt Vadgama; Vineeta Singh; Alexandria Tucker; Javier Collazo; Satyesh Sinha; Amiya Sinha Hikim; Rajan Singh; Shehla Pervin (Hindawi Limited, 2020)
Breast cancer results from a complex interplay of genetics and environment that alters immune and inflammatory systems to promote tumorigenesis. Obesity and cigarette smoking are well-known risk factors associated breast cancer development. Nicotine known to decrease inflammatory signals also modulates immune responses that favor breast cancer development. However, the mechanisms by which nicotine and obesity contribute to breast cancer remain poorly understood. In this study, we examined potential mechanisms by which nicotine (NIC) and high-fat diet (HFD) promote growth of HCC70 and HCC1806 xenografts from African American (AA) triple negative (TN) breast cancer cells. Immunodeficient mice fed on HFD and treated with NIC generated larger HCC70 and HCC1806 tumors when compared to NIC or HFD alone. Increased xenograft growth in the presence of NIC and HFD was accompanied by higher levels of tissue-resident macrophage markers and anti-inflammatory cytokines including IL4, IL13, and IL10. We further validated the involvement of these players by in vitro and ex vivo experiments. We found a proinflammatory milieu with increased expression of IL6 and IL12 in xenografts with HFD. In addition, nicotine or nicotine plus HFD increased a subset of mammary cancer stem cells (MCSCs) and key adipose browning markers CD137 and TMEM26. Interestingly, there was upregulation of stress-induced pp38 MAPK and pERK1/2 in xenografts exposed to HFD alone or nicotine plus HFD. Scratch-wound assay showed marked reduction in proliferation/migration of nicotine and palmitate-treated breast cancer cells with mecamylamine (MEC), a nicotine acetylcholine receptor (nAchR) antagonist. Furthermore, xenograft development in immune-deficient mice, fed HFD plus nicotine, was reduced upon cotreatment with MEC and SB 203580, a pp38MAPK inhibitor. Our study demonstrates the presence of nicotine and HFD in facilitating an anti-inflammatory tumor microenvironment that influences breast tumor growth. This study also shows potential efficacy of combination therapy in obese breast cancer patients who smoke.